Analisis Literatur Review: Problematika Penerapan Kurikulum Merdeka di Sekolah Dasar - Ni ayu made Anita sari; Melani Putria paruru; Nova Wulandari (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
The curriculum occupies a central position in all kinds of educational activities in order to create educational goals. In Indonesia itself, there have been several curriculum changes, and the latest is the Merdeka curriculum. The purpose of this study is to find problems in implementing the independent curriculum and find handling steps or solutions that can be taken to overcome these problems. Using a systematic literature review (SLR) with a qualitative approach or called a meta-synthesis. The literature reviewed in this article is a total of 11 articles found on Google Scholar. Based on the results of the literature study conducted, the implementation of this independent learning curriculum raises various problems, and the most common problem comes from the teacher. The lack of teacher ability and competence is the cause of problems in implementing the independent learning curriculum. To overcome the existing problems, several efforts can be made, such as, the principal and teachers participating in the Merdeka Belajar Curriculum Implementation training to improve the quality of the teachers.